West German industrialists and the making of the economic miracle : a history of mentality and recovery - Grünbacher, Armin 1962- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
West German Industrialists and the Making of the Economic Miracle" investigates the mentality of post-war German (heavy) industrialists through an analysis of their attitudes, thinking and views on social, political and, of course, economic matters at the time, including the 'social market economy' and the fledgling European integration, with this investigation taking place against the backdrop of the 'economic miracle' and the Cold War of the 1950s and 60s. The book also includes an assessment of whether the self-declared, new 'aristocracy of merit' justified its place in society and carried out its actions in a new spirit of political responsibility. This is an important text for all students interested in the history of Germany and the modern economic history of Europe